2017
DOI: 10.1044/2016_ajslp-15-0027
|View full text |Cite
|
Sign up to set email alerts
|

How Much Information Do People With Aphasia Convey via Gesture?

Abstract: It was concluded that all 3 gesture types under investigation contributed to the expression of semantic meaning communicated by PWA. Gestures are an important communicative means for PWA and should be regarded as such by their interlocutors. Gestures have been shown to enhance listeners' interpretation of PWA's overall communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 33 publications
3
22
0
4
Order By: Relevance
“…Most of the earlier research on PWA's gesturing focused on co-speech gestures (e.g., Cocks et al 2013, Coelho 1990, Hogrefe et al 2012 with only a few studies looking at the comprehensibility of these gestures. These studies showed that information in PWA's co-speech gestures can help interlocutors in identifying the message PWA try to convey, as PWA's gestures often convey information not conveyed in speech (de Beer et al 2017, Mol et al 2013, Rose et al 2016.…”
Section: Pantomime's Comprehensibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the earlier research on PWA's gesturing focused on co-speech gestures (e.g., Cocks et al 2013, Coelho 1990, Hogrefe et al 2012 with only a few studies looking at the comprehensibility of these gestures. These studies showed that information in PWA's co-speech gestures can help interlocutors in identifying the message PWA try to convey, as PWA's gestures often convey information not conveyed in speech (de Beer et al 2017, Mol et al 2013, Rose et al 2016.…”
Section: Pantomime's Comprehensibilitymentioning
confidence: 99%
“…These studies showed that information in PWA's co‐speech gestures can help interlocutors in identifying the message PWA try to convey, as PWA's gestures often convey information not conveyed in speech (de Beer et al . , Mol et al . , Rose et al .…”
Section: Introductionmentioning
confidence: 99%
“…This notion entails that gestures can function independently of the speech production system. Neuropsychological evidence on people with speech impairments, such as aphasia, has established that gestures compensate for underspecification in the spoken channel and can function independently of impaired speech (e.g., Akhavan et al, 2018;Akbıyık et al, 2018;de Beer et al, 2017;Göksun et al, 2013Göksun et al, , 2015Hogrefe, Ziegler, Weidinger, & Goldenberg, 2012, 2013aHogrefe, Ziegler, Wiesmayer, Weidinger, & Goldenberg, Differential roles of gestures 4 2013b; Kemmerer, Chandrasekaran, & Tranel, 2007;Kong, Law, Wat, & Lai, 2015;Preisig et al, 2018;Sekine, Rose, Foster, Attard, & Lanyon, 2013, but cf. Cicone, Wagner, Foldi, Zurif, & Gardner, 1979Glosser et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The theme Relying on others or technology confirmed the findings of Moss et al (2004) about people with aphasia taking help from others before publishing text online, and of Sjöqvist Nätterlund (2010) about people with aphasia wanting assistance to access the Internet. The theme Beyond speaking and writing raised questions about how the multimodality of the Internet may be related to the use of gestures described by e.g., de Beer et al (2016). And finally, the theme Controlling speed and timing emphasised the importance of developing asynchronous communication tools to enhance accessibility and thus reduce social exclusion following aphasia (Menger et al, 2016).…”
Section: Stigma Symbols Across Three Dimensionsmentioning
confidence: 99%
“…The signs are not merely words (Barton, 2007;Van Leeuwen, 2005) but also e.g., the media used to communicate or body posture. For people with aphasia, gestures form a crucial part of communicating (de Beer et al, 2016;Sekine & Rose, 2013) and should be recognised as valid signs. Goffman (1963) differentiated types of stigma based on visibility, i.e., whether a stigma is visible to any interaction partner or not.…”
Section: Stigma Symbols As Sign Makingmentioning
confidence: 99%